Next-Generation Influenza HA Immunogens and Adjuvants in Pursuit of a Broadly Protective Vaccine - Kaito A. Nagashima; Jarrod J. Mousa (Viruses, 2021)
Influenza virus, a highly mutable respiratory pathogen, causes significant disease nearly every year. Current vaccines are designed to protect against circulating influenza strains of a given season. However, mismatches between vaccine strains and circulating strains, as well as inferior vaccine effectiveness in immunodeficient populations, represent major obstacles. In an effort to expand the breadth of protection elicited by influenza vaccination, one of the major surface glycoproteins, hemagglutinin (HA), has been modified to develop immunogens that display conserved regions from multiple viruses or elicit a highly polyclonal antibody response to broaden protection. These approaches, which target either the head or the stalk domain of HA, or both domains, have shown promise in recent preclinical and clinical studies. Furthermore, the role of adjuvants in bolstering the robustness of the humoral response has been studied, and their effects on the vaccine-elicited antibody repertoire are currently being investigated. This review will discuss the progress made in the universal influenza vaccine field with respect to influenza A viruses from the perspectives of both antigen and adjuvant, with a focus on the elicitation of broadly neutralizing antibodies.